Optimalisasi Perencanaan Jalan Lingkungan dalam Penanganan Permukiman Kumuh Menggunakan AutoCAD - Elviyanti; Hotter, Robby; Thressia, Merry (Jurnal Informasi dan Teknologi, 2022)
Slum areas really need prevention activities. This activity really requires environmental development planning in housing and residential areas. Environmental quality must also be supported by empowering the community to protect the environment. In Sijunjung Regency there are 31 (thirty one) Slum Housing and Slum Housing locations in 8 (eight) sub-districts. The area is 415.20 (four hundred and fifteen point twenty two) hectares. One of these locations is Nagari Muaro in Sijunjung District. This study aims to reduce slum areas by designing environmental roads as the main basis for development. The locations processed were 3 nagari, namely Muaro in Subarang Ombak with an area of 3.98 Ha; Friday market with an area of 8.46 Ha; and Rimbo Kaluang or Jorong Tangah with an area of 7.31 Ha. This location has a percentage of road surface quality of 85%, namely poor road surface quality. The theory used in planning is Doxiadis namely nature, human environment and networks. Data is processed in a descriptive qualitative analysis by way of observation to interview locations and documentation. The results of this study design environmental roads using Autocad software that can be implemented. So that this research can help design roads in an effort to make settlements healthy by maintaining the social aspects of society.